IMPLEMENTASI MODEL PEMBELAJARAN EBA DI SEKOLAH DASAR PADANG SIDEMPUAN - Lubis, Maulana Arafat; Setiawan, Deny; Br. Perangin-angin, Reh Bungana (JMIE (Journal of Madrasah Ibtidaiyah Education), 2023)
The learning process is the key to student learning success. So that the learning process can be carried out properly, choose the suitable learning model. This is because the learning model is a design pattern aiming to achieve learning and student outcomes and get excellent grades. The research aimed to improve students' Pancasila and Civic Education outcomes in spiritual attitudes, social attitudes, knowledge, and skills by applying the EBA learning model to ethnic, social, and cultural diversity in Indonesia, bound by unity. The research subjects were 30 students of class IV-Zaid SD IT Nurul 'Ilmi Padang Sidempuan. This study used Kurt Lewin's classroom action research method with the stages of planning, action, observation, and reflection in 2 cycles. Data was collected in the form of tests, observations, and interviews. Data were analyzed descriptively qualitatively and quantitatively. The results of the study proved that students experienced an increase in their learning. Before applying the EBA learning model, the average proportion of students' classical Pancasila and Civic Education outcomes obtained a score of 33.33%. After being applied to the first cycle it was 56.66%, and in the second cycle it was 83.33%.